Introducing empiricism - Robinson, Dave (Icon Books, 2004)
Our knowledge comes primarily from experience. But is experience really what it seems? Is it reliable? Empiricist philosophers accept a 'commonsense' view of the phenomena we observe and yet conclude that all we can ever know are 'ideas'. Physical reality may not exist at all! The experimental breakthroughs of Kepler, Galileo and Newton - a radical new outlook in 17th-century science - informed this great British tradition in philosophy. Introducing Empiricism outlines the arguments of Locke, Berkeley, Hume, J.S. Mill, Bertrand Russell, and the last British empiricist, A.J. Ayer. It also looks at criticisms of empiricism in the work of Kant, Wittgenstein, Karl Popper and others.